Effect of HMG extracted from urine of menopausal women on ascorbic acid content of ovaries in immature mice - Al-Ar, rak, J. K. (The Iraqi Journal of Veterinary Medicine, 2000)
The objective of the present investigation to study the effect of (HMG) which extracted from urine of menopausal women according to the method of Albert (1955). The following parameters were studied : 1-Effect of crude hormonal extract on testicular weights of immature mice. 2-Effect of crube hormonal extract on the Ascorbic acid concentrations in ovaries of pseadopregnant mice . The crude hormonal extract from urine of menopausal women caused a significant increase in the testicular weights of immature mice . Administration of crude hormonal extract to pseadopregnant mice significantly decreased their ovarian ascorbic acid content in comparison to the control group. It is concluded that a modified method was developed in it’s preparation resulting in an extract of higher biological activity.